Investigation of exJSRV LTR promoter activity based on transcription factor regulatory networks - Du, Xiaoyue; Zhang, Pei; Duan, Xujie; Bao, Anyu; Ma, Xinqi; Zhang, Yufei; Liu, Shuying (Frontiers in Veterinary Science, 2026)
Ovine pulmonary adenocarcinoma (OPA) is a contagious respiratory tumor affecting sheep and goats, caused by the Jaagsiekte sheep retrovirus (exJSRV). The transcriptional regulation of exJSRV is primarily governed by its long terminal repeat (LTR) region, which interacts with host transcription factors. However, the specific host factors and signaling pathways that modulate exJSRV LTR activity remain poorly understood. To address this knowledge gap, we combined bioinformatic prediction with in vivo and in vivo experiments to identify and validate host transcription factors involved in regulating exJSRV LTR activity. Analyses using the hTFtarget and AnimalTFDB databases identified 53 potential transcription factors interacting with the exJSRV LTR. KEGG enrichment analysis revealed that these factors were mainly associated with the MAPK signaling pathway, particularly the MEK/ERK branch. Activation of this pathway with C16-PAF significantly enhanced exJSRV LTR-driven transcription, while inhibition with U0126 reduced it, indicating a positive regulatory role. Among 18 candidate transcription factors examined, GATA3 exerted the most pronounced effect on transcriptional activity. Overexpression of GATA3 increased both LTR activity and Env protein expression, while GATA3 knockdown reduced them. In vivo, GATA3 overexpression promoted LTR-Env–induced tumor formation in nude mice, whereas GATA3 interference suppressed tumor growth. Furthermore, strong luciferase expression was detected in the lungs and livers of C57BL/6 mice infected with LV-exJSRV LTR-Nanoluc. In conclusion, this study demonstrates that both GATA3 and the MEK/ERK signaling pathway regulate exJSRV LTR activity. Additionally, the exJSRV LTR exhibited potential tendency in the lung and liver tissues of C57BL/6 pairs of mice. These findings provide new insights into the molecular mechanisms underlying OPA pathogenesis.